Iraqi Drinking Water Quality Standards (IQS 417/ 2009) – Revisited - Hala Adnan Abbas (Tikrit Journal of Engineering Sciences)
Iraq was one of the first developing countries to specify standard limits on drinking water quality. In 1967, (Law No. 25/1967) was issued. In 2001, new standard specifications of drinking water quality were issued (IQS/ 417/2001) and revised in 2009. These revisions did not significantly change the numerical limit values of major water quality parameters to reflect any major technological advancement in water quality sciences and epidemiological studies. The aim of this study is to set a numerical limit value for the drinking water temperature parameter to be promulgated and added to law IQS/ 417. Field water samples were collected from different sites in Baghdad. The water source in this study was the Tigris River from three water treatment plants and customer taps at selected districts whose water supplies were fed from these three water treatment plants. These samples’ temperatures were measured by a good-grade mercury-filled Celsius thermometer on site. A literature survey on drinking water temperatures was conducted to collate as much relevant information as possible from countries in the Middle-Eastern region and Europe to compare them with the present results. It was found that the drinking water supply temperature in Baghdad was impacted by the temperature of the water supply source and the pipe distribution network. High averages of drinking water temperature prevailed during the summer season. It is recommended that a temperature limit value for potable water at customer taps should be below 25 ºC, based on health aspects. This recommendation should be promulgated and included in law (IQS/ 417), depending on the public health requirements.